Phycoremediation alternative for shrimp aquaculture effluent management and Islamic perspectives - Mohd Hatta, Farah Ayuni; Othman, Rashidi; Mohd. Yaman, Maheran (Institut Terjemahan & Buku Malaysia Berhad, 2016)
Mangroves forest plays an important role, ecologically and socioeconomically, which should be highly recognized on conservation program. However, mangrove areas of many Asian countries have been cleared for aquaculture activities, in particular, was mainly for shrimp aquaculture. From 1980 to 1990, Peninsular Malaysia also challenged the same problem where it lost 18700 ha due to improper shrimp aquaculture waste management. In 1994, 5790 metric tons of black tiger shrimp were cultured through brackish pond culture which involved 32480 ponds of 2447.34 ha land. Moreover, half of a shrimp’s total weight has consisted of waste products that may increase the nutrients loads especially nitrogen (N) and phosphorus (P). Other possible contaminants produced are cooper (Cu), mercury (Hg), arsenic (As), cadmium (Cd), lead (Pb), zinc (Zn), and aluminum (Al). Consequently, it has led to several environmental problems such as water pollution, mangrove deforestation, and habitat loss. Many technologies such as settling systems, centrifugal systems and mechanical filters had been introduced to treat the wastes, however, it seems ineffective because it produce large amount of sludge deposits, consume high energy, and need frequent maintenance.Therefore, the biology-based technology that is called phytoremediation has been emerging and many studies on this technology have been conducted since the last two decades due to its cheaper approaches than engineering-based technology. Due to ecological function of algae species, it have been suggested as phycoremediator of shrimp aquaculture effluents. Therefore, there are several researches using algae species as biomonitor and biofilter which capable to absorb the extra nutrients and heavy metals. In addition, some principles on sustainability have been highlighted in Al- Quran and As- Sunnah which can guide people in practicing phycoremediation for shrimp aquaculture effluent management.These principles can be a platform for any multidiscipline or institution to introduce better policies in environmental conservation and management through Islamic perspectives.